2016
DOI: 10.1007/s12275-016-6410-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of bacterial diversity in the rhizosphere of tomato by culture-dependent and -independent approaches

Abstract: The microbiome in the rhizosphere-the region surrounding plant roots-plays a key role in plant growth and health, enhancing nutrient availability and protecting plants from biotic and abiotic stresses. To assess bacterial diversity in the tomato rhizosphere, we performed two contrasting approaches: culture-dependent and -independent. In the culture-dependent approach, two culture media (Reasoner's 2A agar and soil extract agar) were supplemented with 12 antibiotics for isolating diverse bacteria from the tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 39 publications
4
41
1
Order By: Relevance
“…The bacterial communities in the five natural field soils DM, JX, HQ, QS and XC, but not the two commercial soils, mostly overlapped with those of the rhizosphere microbiotas in the different cultivar samples. These results were consistent with previous observations of the rhizosphere microbiota of other tomato cultivars, which were dominated by the bacterial orders Sphingomonadales, Rhizobiales, Xanthomonadales, Burkholderiales, Cytophagales and Sphingobacteriales from the bacterial phyla Proteobacteria, Bacteroidetes, and Acidobacteria [15,25]. The result supported the hypothesis that tomato harbors largely conserved communities of rhizosphere microbes that remain stable among cultivars of tomato and even among the field soils from different sources [24][25][26].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The bacterial communities in the five natural field soils DM, JX, HQ, QS and XC, but not the two commercial soils, mostly overlapped with those of the rhizosphere microbiotas in the different cultivar samples. These results were consistent with previous observations of the rhizosphere microbiota of other tomato cultivars, which were dominated by the bacterial orders Sphingomonadales, Rhizobiales, Xanthomonadales, Burkholderiales, Cytophagales and Sphingobacteriales from the bacterial phyla Proteobacteria, Bacteroidetes, and Acidobacteria [15,25]. The result supported the hypothesis that tomato harbors largely conserved communities of rhizosphere microbes that remain stable among cultivars of tomato and even among the field soils from different sources [24][25][26].…”
Section: Discussionsupporting
confidence: 92%
“…The rhizosphere microbiota of the plant is mainly dominated by the bacterial phyla Proteobacteria, Bacteroidetes, and Acidobacteria [2,5,19,20]. In tomato, some studies on the community composition of the rhizosphere microbiota have reached the same conclusion using both culture-dependent and culture-independent approaches [15,[22][23][24][25][26]. Qiao et al [26] found that the three most abundant core phyla in the tomato (Solanum lycopersicum cv.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found an overrepresentation of some Sphingobium and Rhizobium species, suggesting that their abundance could be used as a plant health proxy since we did not observe root rot symptoms in any of our individuals (Satour & Butler 1967). Moreover, in a previous work describing tomato roots microbiomes, Sphingomonas and Sphingobium were detected in more than 50% of the 16S rRNA gene OTUs (Lee et al 2016). Sphingobium has been observed as the dominant genus in tomato roots elsewhere (Pii et al 2016).…”
Section: Discussionmentioning
confidence: 88%